1988
DOI: 10.1021/ac00165a004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microwave-induced plasma as a detector for supercritical fluid chromatography

Abstract: A microwave-induced plasma (MIP) sustained In helium Is evaluated as an element-selective detector for capillary supercritical fluid chromatography (SFC). The plasma source, a surface-mlcrowave-lnduced plasma (surfatron), Is described. Optimal plasma conditions Including viewing position, helium flow rate, and applied microwave power are discussed for sulfur emission In the near-infrared spectral region. In addition, the effects of two common mobile phases (C02 and N20) on plasma stability, sensitivity, and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…The use of a plasma detector in this area requires the ability to produce a mixed gas plasma without sacrificing the analytical performances. Initial experiments with surface wave plasmas as detectors in supercritical fluid chromatography [38][39][40] have shown that a helium-carbon dioxide plasma provides a lower sensitivity for several non-metal analytes than a pure helium plasma. This can be corrected and our own experiments show that for the tin detection in supercritical fluid chromatography, the use of a ternary plasma (He -CO 2 -H 2 ) not only allows the recovery of the analytical sensitivity of the pure helium plasma, but also improves it (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a plasma detector in this area requires the ability to produce a mixed gas plasma without sacrificing the analytical performances. Initial experiments with surface wave plasmas as detectors in supercritical fluid chromatography [38][39][40] have shown that a helium-carbon dioxide plasma provides a lower sensitivity for several non-metal analytes than a pure helium plasma. This can be corrected and our own experiments show that for the tin detection in supercritical fluid chromatography, the use of a ternary plasma (He -CO 2 -H 2 ) not only allows the recovery of the analytical sensitivity of the pure helium plasma, but also improves it (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Successful coupling of either packed or capillary SFC to a modified Beenakker [11], a surfatron [12,13], and microwave plasma torch cavities [14,15] has been described in the literature; the aim of these works was to enable selective detection of compounds containing sulfur [16], chlorine [17 20], and bromine [12,13,18]. In contrast with previous SFC-MIP-AED systems, which were home-made devices, a commercial MIP-AED instrument has recently been successfully hyphenated to packed-column SFC without the modification of the interface used for GC coupling.…”
Section: Introductionmentioning
confidence: 99%
“…While universal response of the flame ionization detector is advantageous in most applications, it is feasible to incorporate certain easily detectable elements during a derivatization step. This strategy has been used in our previous work on thermionic detection of derivatized a-ketoacids 151, steroids 161, and prostaglandins [7], In addition, the element selectivity of a microwave plasma detector [8,9) was explored with the boronate derivatives of certain carbohydrates [ 101. In this communication, we report on the use of nitrogen-sensitive thermionic detector for improved detection of appropriately derivatized oligosaccharides and glycoproteinderived fragments.…”
Section: Introductionmentioning
confidence: 99%